2017
DOI: 10.12691/jfnr-5-9-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Simple Method for Determination of Anti-cancer Component of Indole-3-carbinol in Cabbage and Broccoli

Abstract: Indole-3-carbinol is a potential anti-cancer agent, and it has been found rich in Brassica vegetables.However, there was few good extraction method of indole-3-carbinol in cabbage and broccoli. In this work, the wavelength and the ration of mobile phase in determination method, as well as different temperature and pH values in extraction method were all investigated some cultivars of cabbage and broccoli were collected and validated the determination method. A sensitive and rapid high-performance liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
4
6
0
Order By: Relevance
“…These results are in good agreement with the experimental UV–vis spectra of I3C observing bands at 217 and 277 nm. 34 This affirms that the UV–vis calculating method is reliable. The observable spectrum, that is, the sum of the spectra of all products (total—Figure 4) has two bands, the stronger at 312 nm and the weaker at 504 nm in aqueous medium.…”
Section: Results and Discussionsupporting
confidence: 58%
“…These results are in good agreement with the experimental UV–vis spectra of I3C observing bands at 217 and 277 nm. 34 This affirms that the UV–vis calculating method is reliable. The observable spectrum, that is, the sum of the spectra of all products (total—Figure 4) has two bands, the stronger at 312 nm and the weaker at 504 nm in aqueous medium.…”
Section: Results and Discussionsupporting
confidence: 58%
“…In this step, sonication for several minutes may be used [90]. To complete the hydrolysis of GLS, the mix is then allowed to autolyze at an ambient temperature or is subjected to incubation in a water bath at 35-45 • C for 1-4 h. A buffer solution is typically added instead of deionized water because it affords a constant neutral pH that is required to ensure that GLS hydrolysis yields ITCs [25,87,91,92]. Nevertheless, it has been argued that for SFN, water with a pH of 3-6 should be added to attain the maximum amount of this compound when glucoraphanin is hydrolyzed [19,93].…”
Section: Conventional Extractionmentioning
confidence: 99%
“…For the analysis of ITCs and certain indoles, HPLC coupled with a UV detector has been proposed by various researchers [19,25,78,88,92,93,[95][96][97]99]. For the determination of I3C, indole-3-acetonitrile, and 3,3 -diindolylmethane, HPLC with a Fluorescence Detector (FLD) is usually employed [87,99,143].…”
Section: High-performance Liquid Chromatography (Hplc)mentioning
confidence: 99%
“…It has been reported that I3C is unstable under many conditions such as low pH and high temperature. Under acidic conditions, I3C is rapidly converted into a series of acid condensation compounds [ [8] , [9] , [10] ]. The instability of I3C limits its accurate analysis in broccoli.…”
Section: Introductionmentioning
confidence: 99%